PREVALENCE OF MALNUTRITION AND ASSOCIATED FACTORS IN ELDERLY HEMODIALYSIS PATIENTS AT THONG NHAT HOSPITAL - Thị Lan Hương, Phạm; Huỳnh Thanh Tuấn, Nguyễn; Minh Tiến, Nguyễn; Bách, Nguyễn (Journal of Health and Aging, 2025)
We conducted this study to determine the prevalence of malnutrition and its associated factors among elderly hemodialysis patients at Thong Nhat Hospital, thereby providing evidence to guide nutritional support and dietary interventions. This cross-sectional, descriptive, retrospective, and comparative study included 158 hemodialysis patients at the Department of Nephrology and Dialysis, Thong Nhat Hospital, Ho Chi Minh City. Participants were divided into two groups: those aged ≥60 years and those aged <60 years. Nutritional status was assessed by using body mass index and serum albumin levels. The results showed that the prevalence of malnutrition among elderly hemodialysis patients varied depending on the assessment criteria: 39,82% based on serum albumin levels and 12,9% based on body mass index. Multivariate analysis revealed no statistically significant associations between hypoalbuminemia and diabetes mellitus (OR = 1,30; p = 0,516), hyperparathyroidism (OR = 0,54; p = 0,156), dyslipidemia (OR = 0,81; p = 0,665), hemoglobin levels (OR = 1,01; p = 0,935), duration of dialysis (OR = 1,00; p = 0,672), type of dialysis membrane (OR = 1,30; p = 0,542), or dialysis adequacy (Kt/V) (OR = 1,30; p = 0,355). Our study revealed the prevalence of malnutrition – particularly when defined by serum albumin – is high (39,82%) among hemodialysis patients, especially the elderly. These findings underscore the importance of investigating additional contributing factors to malnutrition in population.